Pengaplikasian Kalman Filter sebagai Pengendali dalam Permainan The Open Racing Car Simulator (TORCS) - Rendy Andrian; Victor; A (Jurnal PROCESSOR, 2020)
The Open Racing Car Simulator (TORCS) works as both a playable game and a framework to develop artificial intelligence-based controllers. As a platform for researchers, TORCS has become a platform in controller development with various approaches in artificial intelligence using sensors and actuators provided by the SCR Server. In this research, the author develops a controller using the Kalman Filter, an algorithm to predict and measure states based on previous measurements to determine future trajectory.